SELF CONCEPT IN RELATION TO EMPLOYEE PERFORMANCE - Samson Laurens (Universitas Dharma Wacana, 2022)
This study aims to analyze the influence of self-efficacy, self-esteem and self-leadership on the performance of employees of the Regional Development Planning Agency of Maluku Province. This study uses a descriptive-quantitative approach with a causal correlation type. The research was conducted at the Regional Development Planning Board of Maluku Province. This research was conducted for 2 (two) months. The population used in this study were all 134 employees of the Bappeda of Maluku Province. Determining the number of samples using Issac and Michael's sample table, where if the population is 134 people, then at a 95% confidence level, the sample is 97 people, which is determined by simple random sampling. Data were analyzed using multiple linear regression analysis.Â The results of the study concluded that (1) self-efficacy has a partial effect on the performance of Bappeda Maluku Province employees, (2) self-esteem has a partial effect on the performance of Bappeda Maluku Province employees, (3) self-leadership has a partial effect on the performance of Bappeda Maluku Province employees (4 ) self-efficacy, self-esteem and self-leadership simultaneously influence the performance of Bappeda Maluku Province employees.